Using standard Bayesian estimation by simulation technique to estimate parameter of Exponential-Rayleigh models - Bakteh, Maral Mohammed; Hussein, Iden Hassan (Iraqi Journal of Science, 2025)
In this paper, the point estimation method for parameters and of the parameters of the Exponential-Rayleigh distribution have been estimated by using the simulation technique by using two Bayesian estimation methods; The first Bayesian method of estimation consists of standard Bayesian estimation methods and the second Bayesian estimation method consists lindley approximation Bayes estimation method to estimate all the unknown parameters of Exponential-Rayleigh distribution. Comparisons between these two methods were made by employing the Mean squares error criterion. Applying a simulation technique with different sample sizes, these methods are being compared. The simulation procedure is used to generate some sample sizes and mean squares error measure, and when we compared between the above two methods, we find that lindley approximation estimation method has the lower Mean squares error.